LEGAL CULTURE IN MULTICULTURALISM AND ITS ROLE IN LAW ENFORCEMENT IN INDONESIA - Agus Suprijanto (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
Multiculturalism in Indonesia can be considered not only as the ancestor’s heritage thatshould be preserved but should also be the main asset in the attempt of nation building.However, incapability of optimizing multiculturalism can be largest constraint that foilsthe achievement of development objective. In this case, legal culture becomes the mainkey to utilizing multiculturalism as the main key to development. Legal culture made as apart of Indonesian legal system will make the society feels being the part of the law itselfand willing to implement the rules of law contained because it is the law that had beeninstitutionalized in the society’s social life previously. The quality of legal culture highlydetermined the law enforce in Indonesia; for that reason the better the integration of legalculture into legal system in Indonesia, the better will be the quality of law enforcement,because basically through a good legal culture, the individual law enforcers will havehigh legal culture that will implement all rules of law without the will to break itoccurring frequently so far. A high-quality legal culture will make judicature a legalprocess that prioritizing justice enforcement, law certainty, justice, social benefit, andsocial empowerment through the judge’s verdict.